2020
DOI: 10.3390/brainsci10040204
|View full text |Cite
|
Sign up to set email alerts
|

Learning a Path from Real Navigation: The Advantage of Initial View, Cardinal North and Visuo-Spatial Ability

Abstract: Background: Spatial cognition research strives to maximize conditions favoring environment representation. This study examined how initial (egocentric) navigation headings interact with allocentric references in terms of world-based information (such as cardinal points) in forming environment representations. The role of individual visuo-spatial factors was also examined. Method: Ninety-one undergraduates took an unfamiliar path in two learning conditions, 46 walked from cardinal south to north (SN learning), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The CN group was more educated that the aMCI and mild AD dementia groups (both p ≤ 0.028). There were more women in the CN and mild AD dementia groups than in the aMCI group (71.8% and 63.6% vs. 44.0%) [χ 2 (2) = 43.21, p = 0.002]. As expected, the CN group had higher MMSE scores (both p < 0.001) and showed better cognitive performance (both p ≤ 0.025) than the aMCI and mild AD dementia groups.…”
Section: Demographic Characteristicsmentioning
confidence: 65%
See 3 more Smart Citations
“…The CN group was more educated that the aMCI and mild AD dementia groups (both p ≤ 0.028). There were more women in the CN and mild AD dementia groups than in the aMCI group (71.8% and 63.6% vs. 44.0%) [χ 2 (2) = 43.21, p = 0.002]. As expected, the CN group had higher MMSE scores (both p < 0.001) and showed better cognitive performance (both p ≤ 0.025) than the aMCI and mild AD dementia groups.…”
Section: Demographic Characteristicsmentioning
confidence: 65%
“…One of them is route learning (i.e., response learning), which entails creating a sequence of body movements (e.g., remembering right, left, right) or creating a series of stimulus–response associations when remembering associations of direction change with a specific landmark (e.g., “Turn left at the shop”) [ 1 ]. This strategy is referred to as egocentric navigation and is primarily based on self-motion perception but can also exploit environmental cues by creating self-to-object relations [ 2 ]. Route learning is primarily supported by the parietal cortex and the caudate nucleus [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 These aforementioned SOTs showed that alternative types of SOTs involving a wider array of objects and presenting higher orders of task complexity were absent in the ATM domain. This could be explained by the fact it has taken almost two decades of intensive psychometric research, involving large samples of participants, to provide strong support for the reliability and validity of SOTs featuring multiple objects (or landmarks) [17][18][19][20][21][22][23][24][35][36][37][38][39] . In general, these SOTs require participants to execute pointing responses toward multiple objects (or landmarks) arranged in an array with reference to an initial heading direction [19][20][21][22][23][24]39 .…”
mentioning
confidence: 99%